EVALUATION OF FUNCTIONAL OUTCOME OF SURGICAL TREATMENT FOR FRACTURE AROUND KNEE WITH LOCKING PLATE - VIKAS KUNTWAD; AMOL WAGH; SATYAJEET A HORE (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim of the study was to evaluate clinical and radiological outcome associated with surgical treatment of fracture around the knee treated by locking plates. Methods: This was an observational follow-up study in which 40 patients who were having fractures around knee (Distal femoral or proximal tibial fractures) and treated by locking plates were included on the basis of a predefined inclusion and exclusion criteria. All patients were surgically treated by locking plates. Functional outcome was assessed by range of flexion, knee score and functional score. Complications such as wound infection, malunion, and non-union were also studied. P value < 0.05 was taken as statistically significant. Results: There was an overall male preponderance with M: F ratio being 1:0.11. Road traffic accidents were responsible for 90% fractures. Average range of knee flexion was 88.5º in patients with distal femur fracture, and 106.5° in patients with proximal tibia fracture. Average Knee society score was 82.35 points in patients with distal femur fracture, and 88.55 points in patients with proximal tibia fracture. There were three cases with non-union, all of them united after secondary bone grafting. Superficial infection was seen in total of two patients. Conclusion: Surgical treatment of fracture around the knee by locking plates gives excellent results in terms of range of flexion as well as functional outcome particularly in cases having extra-articular fractures.